2022
DOI: 10.1080/01490400.2022.2056550
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Leisure Social Support and Flow with Loneliness in International Students in Taiwan: Implications during the COVID-19 Pandemic

Abstract: Loneliness that negatively influences well-being in international students is common, particularly during the COVID-19 pandemic. Leisure may help international students reduce loneliness. To inform efforts to promote well-being for international students, this study examined whether two types of leisure social support (leisure emotional support and leisure instrumental support) and flow while participating in leisure predict loneliness. In total, 332 international students who attended a private university in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…As previous studies have shown, social support has direct and indirect effects on individuals' perceived stress level and overall mental health (Kim, Yun, and Yoon, 2009;Li and Chen, 2014;Ye, 2006aYe, , 2006b. For example, social support serves as a buffer to an individual's stress by offering emotional and other types of support to the individual (Chang, et al, 2022;Cohen and Wills, 1985). Consequently, university students who receive more social support are less likely to experience mental health issues (Hefner and Eisenberg, 2009).…”
Section: Social Psychology Social Support and Social Adjustmentmentioning
confidence: 98%
See 1 more Smart Citation
“…As previous studies have shown, social support has direct and indirect effects on individuals' perceived stress level and overall mental health (Kim, Yun, and Yoon, 2009;Li and Chen, 2014;Ye, 2006aYe, , 2006b. For example, social support serves as a buffer to an individual's stress by offering emotional and other types of support to the individual (Chang, et al, 2022;Cohen and Wills, 1985). Consequently, university students who receive more social support are less likely to experience mental health issues (Hefner and Eisenberg, 2009).…”
Section: Social Psychology Social Support and Social Adjustmentmentioning
confidence: 98%
“…This in turn may worsen the emotional well-being of international students (English, et al, 2022;Hechanova-Alampay, et al, 2002;Yeh and Inose, 2003). Prior research (Chang, et al, 2022;English, et al, 2022) has found that type or quality of social support that international students received had buffering effects when international students were undergoing psychological stress.…”
Section: Social Psychology Social Support and Social Adjustmentmentioning
confidence: 99%
“…The current research investigates the impact of various forms of social support on reducing international students' loneliness using data from a recent survey on Chinese international students at Thai institutions [19]. We discovered through robust estimation of logistic models that co-national ties between Chinese students are more effective at reducing loneliness when they perceive a strong sense of cohesiveness among the Chinese student body at their university.…”
Section: Loneliness Of Life Of Students Studying Abroadmentioning
confidence: 99%
“…It would appear that less well-off Chinese families may find studying in Thailand very alluring due to its proximity and lower cost; in fact, most Chinese students are from the economically underdeveloped Guangxi Zhuang Autonomous Region in southern China [19]. Higher education seems to be a preferred Thai export for Chinese consumers above the rice.…”
Section: Loneliness Of Life Of Students Studying Abroadmentioning
confidence: 99%